Performance of Laying Hens Fed Graded Levels of Soaked Sesame (Sesamum indicum) Seed Meal as a Source of Methionine - Diarra, S.S.; Usman, B.A. (International Journal of Poultry Science, 2008)
In a 12 week experiment the effect of graded levels of soaked sesame seed meal (SSM) as a source of methionine on the performance of laying hens was investigated. In a completely randomized design, 200 black Australorp pullets aged 20 weeks were allotted to 5 isonitrogenous diets with 4 replicates of 10 birds per diet. Sesame seed meal (SSM) replaced soyabean meal (SBM) weight for weight at 0.00, 12.50, 37.50 and 50.00% in diet 1 (control), 2, 3, 4 and 5 respectively. The control diet contained synthetic methionine which was removed with the introduction of SSM in the other diets. The results showed a significant (P< 0.05) reduction in the hen-day egg production above 25.00% and egg weight above 12.50% levels of replacement. Shell quality was not affected by dietary treatment. Feed cost (N/egg) was significantly (P < 0.05) reduced on the 12.50% replacement compared to the 37.50%. There was no treatment effect (P> 0.05) on the while blood cell count, but packed cell volume was significantly (P< 0.05) lowered on the 50.00% and haemoglobin concentration, serum protein, albumin and globulin above 12.50% levels of replacement. These results suggest that replacing SBM with SSM at 12.50% in the diet of laying hens will meet their methionine requirement without adverse effects on performance and health status.